Hubungan antara fraktur maksilofasial dengan terjadinya lesi intrakranial - Tanuhendrata, Anton; Hatibie, Mendy; Oley, Maximillian Ch.; Prasetyo, Eko (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Maxillofacial structure is an unprotected part of the head and is easily exposed to blunt trauma. This structure functions as a safety cushion for the brain when a trauma occures. This study was conducted at Prof. Dr. R. D. Kandou Hospital Manado and aimed to obtain the relationship between maxillofacial fracture and intracranial lesion. Subjects were patients at the emergency unit with traffic accident associated with maxillofacial fracture with or without intracranial lelsion. GCS examination and CT scan of the head were performed to evaluate the intracranial lesion and the maxillofacial fracture (mild, moderate, or severe depended on the type of fracture). Data were tabulated and analyzed with Spearman correlation test using SPSS 2.2 program. The results showed that there were 50 patients with maxilllofacial injury, consisted of: 19 patients with mild injury, 25 patients with moderate injury, and 6 patients with severe injury. There were 13 patients with intracranial lesion and 37 patients without intracranial lesion. The Spearman correlation test showed an X2 = 32,60 and a P < 0.0001. Conclusion: There was a significant correlation between maxillofacial fracture and intracranial lesion.Keywords: maxillofacial fracture, intracranial lesionAbstrak: Struktur maksilofasial merupakan bagian dari tubuh yang tidak terlindungi, mudah terpapar oleh trauma tumpul, dan merupakan bantal pengaman untuk otak saat trauma terjadi. Penelitian ini bertujuan untuk mendapatkan hubungan antara fraktur maksilofasial dengan lesi intracranial dan dilakukan di RSUP Prof. Dr. R. D. Kandou Manado. Subyek penelitian ialah pasien yang datang ke unit gawat darurat yang mengalami kecelakaan lalu lintas dengan fraktur maksilofasial serta ada atau tidaknya lesi intrakranial. Pemeriksaan GCS serta CT scan kepala dilakukan untuk menilai lesi intrakranial sekaligus menilai fraktur maksilofasial (ringan, sedang, atau berat, tergantung dari jenis fraktur). Data ditabulasi dan diuji kemaknaannya dengan korelasi Spearman menggunakan program SPSS 2.2. Hasil penelitian memperlihatkan dari 50 pasien dengan cedera maksilofasial didapatkan: 19 pasien cedera ringan, 25 pasien cedera sedang, dan 6 pasien cedera berat. Terdapat 13 pasien yang disertai lesi intrakranial, sedangkan yang tanpa lesi intrakranial sebanyak 37 pasien. Uji statistik mendapatkan nilai X2 = 32,60 dengan P <0,0001 yang menunjukkan hubungan bermakna antara fraktur maksilofasial dan lesi intrakranial. Simpulan: Terdapat hubungan bermakna antara fraktur maksilofasial dan lesi intrakranial.Kata kunci: Fraktur maksilofasial, lesi intrakranial